The impact of an unexpected wage cut on corruption: Evidence from a "xeroxed" exam - Oana Borcan; Mikael Lindahl; Andreea Mitrut (Institute for the Study of Labor (IZA), 2012)
This paper aims to understand how corruption responds to financial incentives and, in particular, it is an attempt to identify the causal impact of a wage loss on the prevalence of corruption in the education sector. Specifically, we exploit the unexpected wage cut in May 2010 that affected all Romanian public sector employees, including the public education staff, and examine its effect on students' scores on the high-stakes national exam which occurs at the end of high school - the Baccalaureate. To exploit the effect of an income shock on corruption, we use a difference-in-difference strategy and compare the change in the exam outcomes between the public schools - the treatment group - and the private schools - the control group, which were unaffected by the wage cut. Our findings suggest that the wage loss led the public schools to have better exam outcomes than the private schools in 2010 relative to 2009. We attribute this difference to the increased involvement in corrupt activities by public school staff, which was driven by financial incentives. These results match an unprecedentedly high number of allegations of fraud and bribery against school principals, which earned the 2010 Baccalaureate the title of the Xeroxed exam - akin to identical test answers found to have been distributed to numerous students.
Keywords: I2; H7; J3; 330; school principals; bribes; high-stakes tests; Korruption; Lehrkräfte; Besoldung; Bildungsniveau; Vergleich; Privatschule; Schätzung; Rumänien